Smart Sensors for Quality Control: Mechanical Approaches in Food Manufacturing (International Journal of Food and Nutritional Sciences, 2022)
Smart sensors in food manufacturing processes revolutionize quality control with precision, efficiency, and real-time monitoring. These abstract covers smart sensors' mechanical techniques, real-time monitoring, problems, and future possibilities. Smart sensors including vibration, force, pressure, and temperature sensors are crucial throughout the production process. Their mechanical methods protect equipment, apply force precisely, and optimize cooking and sterilization. Providing real-time data feedback and improving quality control, these sensors are essential. Products that are safe to eat and satisfy consumer expectations demonstrate the industry's commitment to quality. However, smart sensor integration is difficult. Technological and cost constraints require continual study and strategic decision-making. These obstacles must be overcome for the sector to fully benefit from smart sensors and improve efficiency and product quality. Future breakthroughs in smart sensor integration are expected. Next-generation sensor technologies, cybersecurity, and sustainability will define this technological evolution. With Industry 4.0 integration, improved data analytics, and training, smart sensors can create a comprehensive, intelligent manufacturing ecosystem.